Scottish modernism and its contexts 1918-1959 : literature, national identity and cultural exchange - McCulloch, Margery Palmer (Edinburgh University Press, 2009)
This innovative book proposes the expansion of the existing idea of an interwar Scottish Renaissance movement to include its international significance as a Scottish literary modernism interacting with the intellectual and artistic ideas of European modernism as well as responding to the challenges of the Scottish cultural and political context. Topics range from the revitalisation of the Scots vernacular as an avant-garde literary language in the 1920s and the interaction of literature and politics in the 1930s to the fictional re-imagining of the Highlands, the response of women writers to a changing modern world and the manifestations of a late modernism in the 1940s and 1950s. Writers featured include Hugh MacDiarmid, Lewis Grassic Gibbon, Neil M. Gunn, Edwin and Willa Muir, Catherine Carswell, Sydney Goodsir Smith and Sorley MacLean. Key Features The first study of a Scottish modernism extending in its impact to the 1950s and drawing on influences from British and European modernism Original perspectives on the literature of the period through discussion of a range of writers and writing genres Detailed consideration of the work of women writers in the context of modernism and in their response to social change A contribution to the expansion of the idea of modernism in its focus both on the modernist artist's role in social and national renewal and on writing from the peripheries of small town, rural and island cultures in contrast to metropolitan culture